Layered double hydroxides as the next generation inorganic anion exchangers: Synthetic methods versus applicability - Chubar, Natalia; Gilmour, Robert; Gerda, Vasyl; Mičušík, Matej; Omastova, Maria; Heister, Katja; Man, Pascal; Fraissard, Jacques; Zaitsev, Vladimir (Advances in colloid and interface science, 2017)
This work is the first report that critically reviews the properties of layered double hydroxides (LDHs) on the level of speciation in the context of water treatment application and dynamic adsorption conditions, as well as the first report to associate these properties with the synthetic methods used for LDH preparation. Increasingly stronger maximum allowable concentrations (MAC) of various contaminants in drinking water and liquid foodstuffs require regular upgrades of purification technologies, which might also be useful in the extraction of valuable substances for reuse in accordance with modern sustainability strategies. Adsorption is the main separation technology that allows the selective extraction of target substances from multicomponent solutions. Inorganic anion exchangers arrived in the water business relatively recently to achieve the newly approved standards for arsenic levels in drinking water. LDHs (or hydrotalcites, HTs) are theoretically the best anion exchangers due to their potential to host anions in their interlayer space, which increases their anion removal capacity considerably. This potential of the interlayer space to host additional amounts of target aqueous anions makes the LDHs superior to bulk anion exchanger. The other unique advantage of these layered materials is the flexibility of the chemical composition of the metal oxide-based layers and the interlayer anions. However, until now, this group of “classical” anion exchangers has not found its industrial application in adsorption and catalysis at the industrial scale. To accelerate application of LDHs in water treatment on the industrial scale, the authors critically reviewed recent scientific and technological knowledge on the properties and adsorptive removal of LDHs from water on the fundamental science level. This also includes review of the research tools useful to reveal the adsorption mechanism and the material properties beyond the nanoscale. Further, these properties are considered in association with the synthetic methods by which the LDHs were produced. Special attention is paid to the LDH properties that are particularly relevant to water treatment, such as exchangeability ease of the interlayer anions and the LDH stability at the solid-water interface. Notably, the LDH properties (e.g., rich speciation, hydration, and the exchangeability ease of the interlayer anions with aqueous anions) are considered in the synthetic strategy context applied to the material preparation. One such promising synthetic method has been developed by the authors who supported their opinions by the unpublished data in addition to reviewing the literature. The reviewing approach allowed for establishing regularities between the parameters: the LDH synthetic method―structure/surface/interlayer―removal―suitability for water treatment. Specifically, this approach allowed for a conclusion about either the unsuitability or promising potential of some synthetic methods (or the removal approaches) used for the preparation of LDHs for water purification at larger scales. The overall reviewing approach undertaken by the authors in this work mainly complements the other reviews on LDHs (published over the past seven to eight years) and for the first time compares the properties of these materials beyond the nanoscale. [Display omitted] •Properties of layered double hydroxides (LDH) are reviewed on the speciation level•The first report to link LDHs materials chemistry with water treatment application•The first critical view on the “memory effect” in context of dynamic adsorption•Exchangeability of the interlayer anions versus atomic scale properties•Physisorbed and interlayer water in LDH versus involvement of the interlayer anions